Development of service restoration algorithm under cold load pickup condition using conservation voltage reduction and particle swarm optimization - Widiputra, Victor; Jufri, Fauzan Hanif; Jung, Jaesung (International Transactions on Electrical Energy Systems, 2020)
The presence of cold load pickup (CLPU) creates a challenge in service restoration owing to an increased load in power systems. To mitigate the effects of CLPU, the system is divided into sections to restore them sequentially. Another approach to solving the CLPU problem is by reducing the total power consumption, with conservation voltage reduction (CVR) as the popular approach to achieve this. This article develops a new restoration algorithm with discrete particle swarm optimization (DPSO) using CVR with CLPU in a power system. DPSO is a global search algorithm that is able to avoid a locally optimal solution. By combining the merits of DPSO and CVR, the restoration time will be improved while maintaining an acceptable operating condition. To verify the algorithm, two simulations are performed. The first simulation compares the proposed algorithm with the tabu search (TS), which shows the improvement in the total restoration time of the system. Then, the second simulation shows an improvement in the restoration time and the ability to maintain the operating voltage during the restoration process by including the CVR in the service restoration.
Keywords: Conservation voltage reductions; Discrete particle swarm optimization; Global search algorithm; Operating condition; Restoration algorithm; Restoration process; Service restoration; Total power consumption; cold load pickup; conservation voltage reduction; discrete particle swarm optimization; service restoration; tabu search